Impact of childhood and maternal vaccination against diphtheria, tetanus, and pertussis in Colombia - María Cristina Hoyos; Doracelly Hincapié-Palacio; Jesus Ochoa; Alba León (SAGE Publishing, 2021)
Background: In Latin America, there are few studies of the impact of vaccination against diphtheria, tetanus, and pertussis. We estimate the impact of infant and maternal vaccination on the incidence of these diseases in Colombia. Design and methods: an interrupted time series study analyzing the incidence before and after of vaccination with DwPT (1975-2018) and with Tdap in pregnant women (2008-2018). A segmented regression model with negative binomial distribution estimated the change in level and trend of the predicted incidence ratio after vaccination in relation to the incidence if vaccination had not been started (IRR), using a Prais Winsten regression. Results: The pertussis IRR decreased immediately after the start of childhood vaccination (0.91, p=0.51), but this was only significant (1.01, p<0.001) along with the trend per year, after the start of maternal vaccination (0.98, p<0.001). In the absence of vaccination, the incidence would not have been reduced. Neonatal tetanus had the highest rate of change with significant reduction -1.69 - CI 95%: -2.91, -0.48). The trend after vaccination was the highest with an annual reduction of 19% (0.81, p=0.001). The change in incidence of diphtheria was significant, although slow (-0.02 - CI 95%: -0.04, -0.004). The sustained effect in the post-vaccination period was smaller (0.95, p=0.79). Conclusions: Childhood and maternal vaccination markedly reduced the incidence of pertussis and neonatal tetanus. It is necessary to maintain optimal vaccination coverage and surveillance, within an integrated elimination plan, which prevents the resurgence of these diseases.